THE ART OF STRATEGY: HOW ORGANIZATIONS CAN ANTICIPATE AND RESPOND TO MARKET CHANGES - Antônio Scapini, Lucas (Revista Gênero e Interdisciplinaridade, 2025)
This study explores the importance of strategic management for organizations to anticipate and respond to market changes in a global context of rapid uncertainties and transformations. The objective was to propose a strategic management model that promotes a proactive posture, integrating tools such as strategic planning, market intelligence and organizational resilience. The relevance of this work is to provide practical insights for companies to develop greater agility and competitiveness, ensuring their sustainability in dynamic environments. The adopted methodology was qualitative, based on recent bibliographic survey, using deductive analysis to connect consolidated theories to contemporary practices. The results indicate that the combination of agile strategies, use of advanced technologies, and visionary leadership is essential to anticipating crises and taking advantage of emerging opportunities. It is concluded that well-structured strategic management allows organizations not only to react, but shape the future of the market, strengthening its competitive position.